Education for Sustainable Development through Subject of Science at Junior Secondary Level: A Study Based on Northern Province of Sri Lanka - Nithlavarnan, A. (The International Academic Forum (IFOR), 2017)
Compared with other countries, Sri Lanka is far behind in focusing on the ESD initiatives and is challenged with the task of embedding ESD at national, school wide and subject levels. This study attempts to examine the present situation of ESD implementation through the subject of Science at junior secondary level in Northern Province of Sri Lanka. A mixed research design used both primary and secondary data. Principals, 136 science teachers, and 397 Grade 9 students from 58 secondary schools in Northern Province of Sri Lanka were taken as the survey sample. The science curriculum has incorporated cognitive content that has received more emphasis than the skill and value components. Likewise, environmental aspects to a greater extent have been given more emphasis than economic elements and socio cultural elements. According to the change agents' perceptions, some issues are still adversely affecting the sustainability within the Province. The study observed, that interviewees do not seem to have a clear understanding of the concept of SD. Few numbers of change agents have acquired training on ESD directly. Students at junior secondary level indicated a fair to strong understanding on knowledge, attitudes and behavior as features of SD. Further students appeared to have positive attitudes and a favorable behavior concerning different aspects of SD related to science. There were several ESD good practices implemented within the classrooms and the school environment related to science. This study also identified problems and its strategies for addressing those issues on implementation of ESD through junior secondary Science.
Keywords: Education for Sustainable Development; Science; Junior Secondary Level; Northern Province of Sri Lanka